Bridging the gap between industry and academia: Establishing an industry advisory board in Ecuador’s higher education system - Van Hoof, Hubert B.; Galarza-Torres, Alexandra; Sánchez-Rodas, Lourdes M.; Eljuri J., María-Isabel; Jaramillo-Granda, Marlene (Maskana, 2017)
Considering the recent changes regarding curriculum redesign in Ecuador’s higher education, as stipulated in the Ley Orgánica de Educación Superior (LOES), this article discusses the benefits of the creation of an industry advisory board in a professional hospitality and tourism management program. Based on a review of the literature, the article argues that an industry advisory board is helpful in creating employment opportunities for students, research opportunities for faculty and engaging alumni in the academic program. Its members can provide academic programs with information on the latest industry trends and assist them in enhancing their community outreach efforts.